1983
DOI: 10.1128/aac.23.3.497
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro study of teichomycin A2

Abstract: Teichomycin A2 was evaluated in vitro against clinical isolates, and its activity was compared with that of other antibiotics. This compound was very active against all organisms tested; its activity was comparable to that of vancomycin, and it was superior to several other antibiotics when tested against gram-positive cocci. Because of its in vitro activity, it deserves clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 8 publications
(8 reference statements)
1
19
0
1
Order By: Relevance
“…Teichomycin A2 and vancomycin have shown similar in vitro interactions with rifampin in combination tests (7). A more recent study also demonstrated that teichomycin A2 is highly active against methicillin-resistant S. aureus strains but less active than vancomycin against S. epidermidis strains (5).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Teichomycin A2 and vancomycin have shown similar in vitro interactions with rifampin in combination tests (7). A more recent study also demonstrated that teichomycin A2 is highly active against methicillin-resistant S. aureus strains but less active than vancomycin against S. epidermidis strains (5).…”
Section: Resultsmentioning
confidence: 82%
“…Teichomycin A2 and aminoglycoside'combinations also produced higher bacteriostatic and bactericid'al synergistic activities than did vancomycin combined with an aminoglycoside against S. faecalis isolates. Teichomycin A2 has been tested in vitro against a wide spectrum of gram-positive organisms (4,5,8,11). In one study, of 25 strains each of S. aureus and S. epidermidis, teichomycin A2 had an activity similar to that of vancomycin (4).…”
Section: Resultsmentioning
confidence: 99%
“…Like vancomycin, it is active against gram-positive aerobic and anaerobic bacteria, including methicillin-resistant staphylococci (6,8,9,21,(24)(25)(26). The in vivo activity of teicoplanin for serious staphylococcal infections has been established in experimental animal models (5,10,23).…”
mentioning
confidence: 99%
“…Teicoplanin is a parenteral glycopeptide antibiotic with an antibacterial spectrum like that of vancomycin (1,9). Unlike vancomycin, teicoplanin is well tolerated after intramuscular administration.…”
mentioning
confidence: 99%